Radiological Examination of The Maxillary Bone to Detect Alveolar Bone Loss in Orchidectomized Cats (Felis catus) - Adrianus, Annisa Almafitri; Waskita, Pranyata Tangguh; Hartady, Tyagita (Jurnal Sain Veteriner, 2025)
This study aims to determine the potential impact of orchidectomy on alveolar bone density in male cats, using an exploratory research design and the CEJ-ABC distance measurement method. This study involved four different groups based on duration since orchidectomy, with maxillary radiographic images used to assess the degree of alveolar bone loss. The results, as determined by one-way ANOVA test, showed no statistically significant differences in CEJ-ABC distances between orchidectomy groups for the measured surfaces (mesial PM3, distal PM3, mesial PM4, and distal PM4), with all p -value exceeds 0.05. Consequently, the null hypothesis, indicating no substantial difference in alveolar bone density between orchidectomy groups, can be accepted.Keywords: alveolar bone loss, CEJ-ABC distance, orchidectomy